Pendampingan Lalaran Nadhom Untuk Meningkatkan Ingatan Hafalan Santri As-Sunniyyah Kencong Jember - Ghofur, M Abdul; Intan, Dewi Nur (INAIFAS Press, 2023)
Memorization is a level of knowledge that is carried out regularly to increase understanding, recitation is one way to attach memorization. At the As-Sunniyyah Kencong Jember Islamic Boarding School, there are several marhalah classes, lower (ibtida'iyah), middle (tsanawiyah) and upper (aliyah). Class 2 tsanawiyah memorizes nadzom tajwid (jazariyah) and nahwu (jurumiyah). The aim of this Community Service activity is to empower the As-Sunniyyah Islamic Boarding School students in memorizing the obligatory nadzom. The students became enthusiastic in memorizing the mandatory nadzom which was carried out in the classes of the assisted participants, apart from that, the students were able to understand the contents of the memorized nadzom. Memorizing an obligation, The result of this mentoring is that by using the lalaran method, the students will easily memorize a nadzom that is required for each marhalah which must be deposited with their respective ustadz councils